If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15x-x2=3x-15
We move all terms to the left:
15x-x2-(3x-15)=0
We add all the numbers together, and all the variables
-1x^2+15x-(3x-15)=0
We get rid of parentheses
-1x^2+15x-3x+15=0
We add all the numbers together, and all the variables
-1x^2+12x+15=0
a = -1; b = 12; c = +15;
Δ = b2-4ac
Δ = 122-4·(-1)·15
Δ = 204
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{204}=\sqrt{4*51}=\sqrt{4}*\sqrt{51}=2\sqrt{51}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(12)-2\sqrt{51}}{2*-1}=\frac{-12-2\sqrt{51}}{-2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(12)+2\sqrt{51}}{2*-1}=\frac{-12+2\sqrt{51}}{-2} $
| X2+4x-11=0 | | 7(t-4)-2=4(t-3) | | 2*z/3-7=-9 | | 3X+5k=18 | | 20=4(g-15) | | X2-6x=-5 | | -13=(9/5)c+32 | | 10-6y=7 | | 1/3(6b+9)+b=0 | | 6=w-84/2 | | 20=4g(g-15) | | 63=31-4(x-3) | | 2(p-14)=2 | | -2x+6x+26=3x-22 | | 2(p-4)=2 | | 6b^2=b^2+7-b | | 4(x-5)+4x=-24+2x | | h=16^2+48+3 | | 6(t-88)=24 | | −2+5x=4x+2 | | h+72/2=3 | | 3=j/3-5 | | 3x+6-4x=24+5x | | s+6/9=3 | | 5(g-74)=90 | | 70+35h=1 | | q+27/9=7 | | 6=z-56/7 | | 2b=5=19 | | 3=−15c+8 | | 50-2x=24 | | 9x/4=6 |